Protein Kinase D-mediated Phosphorylation and Nuclear Export of Sphingosine Kinase 2 - Ding, Guo; Sonoda, Hirofumi; Yu, Huan; Kajimoto, Taketoshi; Goparaju, Sravan K.; Jahangeer, Saleem; Okada, Taro; Nakamura, Shun-ichi (The Journal of biological chemistry, 2007)
Sphingosine kinase (SPHK) is a key enzyme producing important messenger sphingosine 1-phosphate and is implicated in cell proliferation and suppression of apoptosis. Because the extent of agonist-induced activation of SPHK is modest, signaling via SPHK may be regulated through its localization at specific intracellular sites. Although the SPHK1 isoform has been extensively studied and characterized, the regulation of expression and function of the other isoform, SPHK2, remain largely unexplored. Here we describe an important post-translational modification, namely, phosphorylation of SPHK2 catalyzed by protein kinase D (PKD), which regulates its localization. Upon stimulation of HeLa cells by tumor promoter phorbol 12-myristate 13-acetate, a serine residue in a novel and putative nuclear export signal, identified for the first time, in SPHK2 was phosphorylated followed by SPHK2 export from the nucleus. Constitutively active PKD phosphorylated this serine residue in the nuclear export signal both in vivo and in vitro. Moreover, down-regulation of PKDs through RNA interference resulted in the attenuation of both basal and phorbol 12-myristate 13-acetate-induced phosphorylation, which was followed by the accumulation of SPHK2 in the nucleus in a manner rescued by PKD over-expression. These results indicate that PKD is a physiologically relevant enzyme for SPHK2 phosphorylation, which leads to its nuclear export for subsequent cellular signaling.